Economic Impact on Micro, Small and Medium Enterprises (MSMEs ) Due to Forest and Land Fires in Kutai Kartanegara Regency - Noor Ramsyah; Rahcmad Budi Suharto; Juliansyah Roy (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Forest and land fires (karhutla) are recurring disasters that cause serious economic impacts on Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the direct and indirect economic impacts of karhutla on MSMEs in Kutai Kartanegara Regency. A quantitative approach was applied through a survey of 150 respondents across five districts, analyzed using descriptive statistics, the Wilcoxon Signed-Rank comparative test, and multiple linear regression. The results prove a highly significant difference in net income before and after the disaster (Z = -7.126; p = 0.000). The heaviest losses were borne by smallholder oil palm farmers in rural areas, while urban areas remained relatively stable. Indirect impacts were transmitted through a health crisis (acute respiratory infection) that triggered treatment costs and loss of productive working days. The regression model (R² = 0.524) shows that disaster exposure has a dominant negative effect, while business adaptation and the institutional role of local government (the Kredit Kukar Idaman program) have a significant positive effect on income recovery.